Pelatihan Marketing Online dan Workshop E-Commerce untuk Meningkatan Pemasaran pada Kelompok Pengrajin Rotan Kota Pekanbaru - Nurliana Nasution; Feldiansyah Bakri Nasution; Mhd Arief Hasan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
UMKM have been regulated in the legal umbrella based on the law. Some examples of SMEs include: Culinary Sector - Selling snacks, fried foods, selling food, opening a restaurant, opening a small restaurant or opening a cafe business. Examples of UMKM in the Fashion Sector - small-scale clothing stores, distributions that sell special clothing for young people, batik shops, Muslim clothes and so on. Atang Rattan Furniture Business is one of the MSMEs engaged in rattan handicrafts. This rattan craftsman has been pioneered from generation to generation from the previous generation. Pulau Cinta is the name of a natural tourist attraction located 30 KM from Pekanbaru City Center. Rattan furniture makes various business models of rattan crafts including woven furniture, bed frames, bookcases, shoe racks, bags, wallets, lampshades, rattan pillows, chairs, tables and others. This place also accepts craft orders as needed. This MSME has 15 employees. The resulting product is marketed in the city of Pekanbaru, Riau, to several areas in Sumatra. In 2020 there was an outbreak (Endemic) of Covid-19) in all regions of Indonesia and even abroad. This has a negative impact on the global economy which is also felt by all levels of society. Including MSMEs, Atang Rattan Furniture experienced a drastic decline in the number of sales figures. Even though they also have to incur operational costs such as employee salaries, maintenance costs, production and others. the average sales of Product Items decreased drastically. On average, more than 50 to 60 percent of turnover per item fell. The priority issues in this community service 1). Decrease in Sales 2) Do not have a good marketing strategy We provide solutions including Understanding the Importance of Online-Based Sales, E-Commerce Online Sales Workshops.